Electrochemical impedance spectroscopy of a Li–S battery: Part 1. Influence of the electrode and electrolyte compositions on the impedance of symmetric cells. (1st August 2017) - Conder, Joanna; Villevieille, Claire; Trabesinger, Sigita; Novák, Petr; Gubler, Lorenz; Bouchet, Renaud
Graphical abstract: Highlights: Electrochemical impedance spectroscopy (EIS) study of symmetric cells. Separation of the positive and negative electrode EIS contributions. Li electrode/electrolyte interface as a function of the electrolyte composition. Blocking-like behavior of the sulfur-containing positive electrode. Binder properties hidden in the medium- to low-frequency region. Abstract: Symmetric cells comprising either a pair of positive (sulfur), blocking or negative (lithium) electrodes were investigated by means of electrochemical impedance spectroscopy, to break down the complexity of the lithium–sulfur chemistry and to understand how the individual cell components influence the transport properties of a full cell. We thoroughly analyzed the ageing of the negative electrode (lithium metal) interface under open circuit conditions as a function of the nature of species present in the electrolyte, including the influence of dissolved binder and/or long-chain polysulfides. In a similar manner, we investigated the positive electrode interface. Herein, the objective was to understand the impact of an individual electrode component on the impedance response of the symmetric cell, and, more importantly, to discern the role of the sulfur in charge transfer reaction(s).